PENGARUH JOB CHARACTERISTIC TERHADAP SEMANGAT KERJA PEGAWAI - Masharyono, Masharyono (Program Studi Akuntansi FPEB UPI, 2015)
The role of human resources in an organization that is increasingly important with the increasing complexity of tasks, responsibilities, and challenges facing today's organizations. High-quality workforce one of which is driven by high morale. Thus will contribute to the advancement and survival of the organization. One of the factors that affect morale is a factor characteristics of the job is a factor that will make employees have a high morale.